Interplay between viruses and bacterial microbiota in cancer development. (August 2017) - Vyshenska, Dariia; Lam, Khiem C.; Shulzhenko, Natalia; Morgun, Andrey
Highlights: Microbiota help in protecting mammals from oncogenic viruses. Helicobacter species can aid HBV and HCV carcinogenesis. Bacterial vaginosis and sexually transmitted infections may promote HPV and HIV driven cancers. Bacteria-derived butyric acid can reactivate latent oncovirus infections. P. gingivalis can synergize with HIV and herpesviruses leading to oral cancer. Abstract: During the last few decades we have become accustomed to the idea that viruses can cause tumors. It is much less considered and discussed, however, that most people infected with oncoviruses will never develop cancer. Therefore, the genetic and environmental factors that tip the scales from clearance of viral infection to development of cancer are currently an area of active investigation. Microbiota has recently emerged as a potentially critical factor that would affect this balance by increasing or decreasing the ability of viral infection to promote carcinogenesis. In this review, we provide a model of microbiome contribution to the development of oncogenic viral infections and viral associated cancers, give examples of this process in human tumors, and describe the challenges that prevent progress in the field as well as their potential solutions.